Методи та засоби опрацювання сигналів при дослідженні спектрального імпедансу елементів промислових систем - Стрілецький, Юрій Йосипович (Івано-Франківський національний технічний університет нафти і газу, 2018)
У дисертації започатковано нові та розвинуто вже відомі теоретичні і методологічні засади в області цифрового опрацювання сигналів у комп’ютерних системах неруйнівного контролю, зокрема компонентах спектрального аналізу масивів дискретизованих даних, компонентах формування завадостійких сигналів збудження і їх опрацювання в інформаційно-вимірювальних каналах. Запропоновано методи опрацювання дискретизованих вимірювальних сигналів, що формуються в результаті взаємодії контрольованого середовища із зовнішнім збуджуючим сигналом, на основі чого визначається спектральний імпеданс середовища як відношення спектральних щільностей опрацьованих сигналів. Розвинено теорію спектрального аналізу дискретизованого сигналу шляхом рекурсивної побудови регресійної моделі сигналу у вигляді лінійної комбінації гармонійних сигналів. На основі запропонованих методичних підходів реалізовано готові технічні рішення у вигляді спецпроцесорів, які дають можливість створювати спеціалізовані інформаційно-вимірювальні системи неруйнівного контролю із більшою інформативністю. The thesis launched new and developed already known theoretical and methodological principles in the field of digital signal processing in computerized systems of non-destructive testing, including components of spectral analysis of sampled data arrays, components of noise-proof excitation signal generation and their processing in the information-measuring channels necessary for propagation a generalization approach to the creation of new means of non-destructive control of industrial objects. Processing methods of discrete measurement signals, which are formed as a result of interaction of a controlled medium with external excitatory signal, are proposed. Using these methods the spectral impedance of the medium is determined as the ratio of spectral densities of processed signals obtained in the form of excitation and response. The theory of spectral analysis of discrete signal is developed by recursive construction of regression signal model in the form of linear combination of harmonic signals, which made it possible to increase the accuracy of frequency components representation, reducing influence of the discreteness in time domain. Presentation of response signal from physical object in form of a regression model was used for designing the method of determining parameters of spectral component in the noisy signal by recursive analysis of interaction of extraneous spectral components with a synchronous pair of harmonic excitation signals. Signal description in form of regression model constructed using the values of the sampled signal obtained during free vibrations of physical objects was used to reproduce the time variations of the amplitude of the individual spectral components and to increase the informativeness of signal representation which is necessary for the investigation of mechanical properties of objects. The proposed method of reproduction of one period of a separate spectral component by its fragment increased the informativeness of the estimation of its amplitude in the aggregate sampled signal. The developed method of exciting oscillations in a physical system by use of frequency selective feedback allowed identifying the characteristic frequencies of the investigated mechanical object and diagnosing by their ratio the damages associated with energy absorption during cyclic deformation. Propagation of concept of spectral impedance to assess the thermal properties of metal and application of digital methods for processing signals obtained during the measurement of heat flows in the nonstationary mode allowed to develop a method for detecting the local change in the heat conductivity of the metal parts that arose as a result of damage. Based on the proposed methodical approaches technical solutions are realized in the form of special processors that make it possible to create specialized information-measuring systems of non-destructive control with greater informativity. The special processors are designed for signal processing for reproducing the shape of noise-distorted signal and its synchronous demodulation, the search for small phase angles of noisy signals, digital synthesis of the harmonic waveform and its subsequent transformation in order to improve spectral purity and for processing of periodic signals obtained from thermal field transformation into an electrical signal. Thus, a methodological and hardware basis for the use of spectral evaluation of the properties of industrial objects in the tasks of non-destructive control was created. В работе предложены новые и развиты уже известные теоретические и методологические основы в области цифровой обработки сигналов в компьютерных системах неразрушающего контроля, в частности компонентах спектрального анализа массивов дискретизированных данных, компонентах формирования помехоустойчивых сигналов возбуждения и обработки сигналов откликов в информационно-измерительных каналах. Разработаны методы обработки дискретизированных измерительных сигналов, формируемых в результате взаимодействия контролируемой среды с внешним возбуждающим сигналом, на основании чего определяется спектральный импеданс среды как отношение спектральных плотностей обработанных сигналов. Развита теория спектрального анализа дискретизированного сигнала путем рекурсивного построения регрессионной модели сигнала в виде линейной комбинации гармонических сигналов. На основе предложенных методических подходов реализованы готовые технические решения в виде спецпроцессоров, позволяющих создавать специализированные информационно-измерительные системы неразрушающего контроля с большей информативностью.
Signal processing methods and means in spectral impedance investigation of industrial systems elements
Методы и средства обработки сигналов при исследовании спектрального импеданса элементов промышленных систем
Keywords: спектральний імпеданс; спектральна щільність сигналу; лінійна регресія; кореляційний аналіз; кореляційний фільтр; цифровий синтез сигналу; множина спектральних оцінок; тепловий імпеданс; spectral impedance; spectral density of a signal; linear regression; correlation analysis; correlation filter; digital signal synthesis; spectral estimates of signal; thermal impedance; спектральный импеданс; спектральная плотность сигнала; линейная регрессия; корреляционный анализ; корреляционный фильтр; цифровой синтез сигнала; множество спектральных оценок; тепловой импеданс; 004.62:681.2.083:621.37:539.3:536.6